THE EFFECT OF PERCEPTION AND ACADEMIC SELF-EFFICACY ON DISORIENTATION IN ECONOMICS LEARNERS IN MAN CITY OF MOJOKERTO - Mohamad Mujahid Islamudin; Abdul Bashith (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the influence of student perception and academic self-efficacy on disorientation in economics learning among class XI IPS students of MAN Kota Mojokerto. Disorientation in learning, characterized by confusion, loss of learning direction, and unclear learning objectives, is a significant issue that impacts students' low motivation and academic achievement. This study uses a quantitative explanatory approach with a sample of 80 respondents selected using the Slovin formula. Data were collected through a closed Likert-scale questionnaire that has been tested for validity and reliability. Data analysis was carried out through classical assumption tests and multiple linear regression to determine the partial and simultaneous effects of the two independent variables on disorientation in economics learning. The results showed that academic self-efficacy had a negative and significant effect on disorientation in learning (0.005, which is less than (p < 0.05), which means that the higher the academic self-efficacy, the lower the level of disorientation experienced by students. Conversely, student perception did not have a significant effect on disorientation in learning (0.922, which is greater than (p > 0.05). These findings indicate that internal factors, such as self-confidence, play a stronger role in determining the direction and clarity of students' learning goals. This study concludes that strengthening academic self-efficacy is essential to reduce disorientation and increase the effectiveness of economics learning.